Anti-allergic activity of glycyrrhizic acid on IgE-mediated allergic reaction by regulation of allergy-related immune cells - Shiwen Han (Nature Portfolio, 2017)
Abstract Glycyrrhizic acid (GA), the major bioactive triterpene glycoside of glycyrrhiza, has been shown to possess a wide range of pharmacological properties, including anti-inflammatory and anti-viral properties. However, few studies have examined the anti-allergic activity and exact mechanism of action of GA. In the present work, the anti-allergic activity and possible mechanisms of action of GA on an immunoglobulin (Ig) E-mediated allergic reaction has been studied using three models of allergic reaction in vivo and in vitro. Active systemic allergic reaction in Balb/c mice showed that GA can suppress the increased level of IL-4 to restore the immune balance of TH1/TH2 cells in a dose-dependent manner. Additionally, GA attenuated significantly the B cells producing allergen-specific IgE and IgG1 partly because of the low levels of TH2 cytokines. Both passive cutaneous anaphylaxis in vivo and an RBL-2H3 cell-based immunological assay in vitro indicated that GA acted as a “mast cell stabilizer”, as it inhibited mast cell degranulation and decreased vascular permeability by inhibiting the expression of Orai1, STIM1 and TRPC1, which blocked extracellular Ca2+ influxes. The current study suggests that GA may serve as an effective anti-allergic agent derived from food for the prevention and treatment of IgE-mediated allergic reaction.